Medical Jargons used by the Paramedics of Primary Health Care (PHC) in Tarano - Istianti, Hadijah; Tarihoran, Irfan Hamonangan (STKIP Yapis Dompu, 2022)
This study aims to obtaining knowledge of medical worlds or some terms of medical jargons used by the paramedics of Primary Health Care (PHC) in Tarano. Overall, the problem identified in this study is that how the form, meaning, and function of medical jargons are used by the PHC in Tarano. In this study, qualitative descriptive method is employed in analyzing the data. There are 15 terms identified within the paramedic’s conversation that is recorded during the study. To collect the data, three techniques are applied, i.e. transcription, observation and interview. The conversations are transcribed and observation sheet is applied during the observation. Meanwhile, the process of interview is recorded. Thus, all data from transcription, observation and interview are analyzed. The results of study show that the terms in the medical jargons are classified into three points, those are the form, meaning, and function of terms in the medical jargons. Firstly, the form of the terms in the medical jargons is analyzed based on the term source of language and how it derives. The term sources or language element of the medical jargons i.e. Indonesian common vocabulary and foreign language vocabulary. Furthermore, the process of the medical jargons formation consists of three forms, i.e. single, complex, and abbreviation which comprise of shorting, fragment, and acronym. Secondly, the meaning of the medical jargons found is the term meaning since its meaning is definite, clear, and unambiguous even without the context of the sentence. Lastly, there are three functions of the medical jargons used by the paramedics in Primary Health Care (PHC) in Tarano, i.e. informative function, heuristic function, and regulation function.